Heparin- and sulfatide-binding peptides from the type I repeats of human thrombospondin promote melanoma cell adhesion. - Guo, N H (1992)
Peptides from the three type I repeats of human endothelial cell thrombospondin, containing the consensus sequence-Trp-Ser-Xaa-Trp-, bind to sulfated glycoconjugates including heparin and sulfatide. The peptides are potent inhibitors for the binding of thrombospondin, laminin, or apolipoprotein E to these ligands. The thrombospondin peptides that inhibit heparin binding, but not adjacent peptides from the thrombospondin sequence containing the previously identified adhesive motif Val-Thr-Cys-Gly, promote melanoma cell adhesion when immobilized on plastic. Melanoma cell adhesion to the immobilized peptides is inhibited by soluble recombinant heparin-binding fragment of thrombospondin. The peptides also inhibit heparin-dependent binding of thrombospondin or laminin to human melanoma cells. The active peptides lack any previously identified heparin-binding consensus sequences and most do not contain any basic amino acids. Studies with homologous peptides showed that the tryptophan residues are required for binding. Adjacent basic residues in the second type I repeat enhance binding to heparin but not to sulfatide. Thus the type I peptides of thrombospondin define a distinct class of heparin-binding peptides.